2016
DOI: 10.1007/s40789-016-0103-8
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption properties of CFBC ash–cement pastes as compared with PCC fly ash–cement pastes

Abstract: Circulating fluidized bed combustion (CFBC) ash can be potentially used as supplementary cementitious materials for concrete production due to its desirable pozzolanic activity. The adsorption properties of CFBC ash-cement pastes were studied, and ordinary pulverized coal combustion (PCC) fly ash-cement pastes were used as control. The water-adsorption and superplasticizer (SP)-adsorption properties of the pastes were evaluated by water demand and UV-visible absorption spectroscopy respectively. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Testing the consistency of cement–ash mortars containing FBC fly ash of different origins, as well as mixes of FBC and siliceous fly ashes (from ZII to ZX, Figure 8 ) showed that mortars containing FBC fly ashes required an increased quantity of water to reach the consistency of the reference mortar (slump cone 5 ± 0.5 cm) compared to the reference mortar (ZI) made of Portland cement. The increased water demand for mortars with FBC fly ashes was also pointed out in [ 23 , 34 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 77%
“…Testing the consistency of cement–ash mortars containing FBC fly ash of different origins, as well as mixes of FBC and siliceous fly ashes (from ZII to ZX, Figure 8 ) showed that mortars containing FBC fly ashes required an increased quantity of water to reach the consistency of the reference mortar (slump cone 5 ± 0.5 cm) compared to the reference mortar (ZI) made of Portland cement. The increased water demand for mortars with FBC fly ashes was also pointed out in [ 23 , 34 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 77%
“…FBC fly ashes compose mainly of irregularly or angularly shaped particles [38,39] in contrast to tradiotional PCC fly ash which are mainly spherical [40] (see example from Figure 4). Spherical particles can be found also from some FBCFAs, but their share is much lower.…”
Section: Morphological Propertiesmentioning
confidence: 99%
“…The high f-CaO content in CFFA causes it to react violently with water and derive self-cementing properties [ 14 ], which makes CFFA a feasible substitute for cement. The small number of studies that partially replaced cement with CFFA found that it generally reduces the compressive strength of the cementitious material, increases flowability, and delays the setting time [ 15 , 16 , 17 ]. Based on existing research, CFFA does not yet meet the construction regulations reached by original fly ash.…”
Section: Introductionmentioning
confidence: 99%